Pengaruh Peningkatan Efisiensi Pemasangan Heatsink pada Panel Photovoltaic Tipe Polycrystalline - Charles Sjahruddin; Irwin Bizzy (Jurnal Rekayasa Mesin, 2020)
Photovoltaic panels are equipment that can convert solar energy into electrical energy. Theefficiency of this panel decreases as the temperature rises, so cooling media is needed to increaseits efficiency. This study uses a polycrystalline type panel with a cooling medium in the form of aheatsink that is placed behind the panel. The results showed an increase in efficiency of 3.37% withan average output power of 0.483 W. The average convection heat transfer coefficient was 4.18W/m2.K when using a heatsink and without using a heatsink was 4,31 W/m2.K.